Looking for a successful translocation: the case of Astragalus edulis - Bobo Pinilla, Javier; López-González, Noemí; Caballero, Armando; Peñas de Giles, Julio (Mediterranean Botany, 2021)
Astragalus edulis (Fabaceae) is an endangered annual plant species from the western Mediterranean region. It occurs in the Iberian Peninsula (SE), Morocco (two main locations in the NE and SW), and the easternmost Canary Islands (Lanzarote and Fuerteventura). After a thorough study assessing genetic diversity and phylogeographic patterns, and a proposal of a management plan to preserve the genetic diversity across the entire area of the species, it is about time to go further in the species conservation. It is necessary to recognize genetically impoverished populations to be able to successfully reinforce populations and find realistic places for translocations. For this, Nei’s genetic diversity values were calculated for the three geographic areas and for their populations. Diversity values were further evaluated to calculate the optimal contribution for the populations within each area to maximize the genetic pool. To evaluate whether the optimum habitat for the species is expected to grow or decrease under a climate change scenario, the optimal model of current climatic suitability of A. edulis was projected into the IPCC (2070_RCP8.5) future scenario. The different geographical areas showed similar genetic diversity values. The populations that contribute to maximize the genetic pool in each geographic area were similar, but not equal, to those proposed in previous studies. The future potential habitat for the species shows a significant range decline, which will affect translocation efforts.